2010
DOI: 10.1111/j.1600-6143.2010.03256.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Once Daily (ADVAGRAF) Versus Twice Daily (PROGRAF) in De Novo Renal Transplantation: A Randomized Phase III Study

Abstract: This multicenter, 1:1-randomized, parallel-group, noninferiority study compared the efficacy and safety of twice-daily tacrolimus (Tacrolimus BID; Prograf) and once-daily tacrolimus prolonged release (Tacrolimus QD; Advagraf), combined with steroids and low-dose mycophenolate mofetil without antibody induction, in 667 de novo kidney transplant recipients. A doubleblind, double-dummy 24-week period was followed by an open extension of up to 12 months posttransplant. Biopsy-proven acute rejection rate at 24 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
135
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 26 publications
12
135
5
Order By: Relevance
“…Increasing pill burden is associated with decreased adherence [20,21], and lack of adherence is associated with acute rejection [22,23] and graft loss [21,[24][25][26]. While there are currently available prolonged-release tacrolimus hard capsule formulations designed for once-daily dosing, data from these formulations do not suggest that they offer improved bioavailability over tacrolimus twice-daily capsules [27][28][29]. In a clinical trial in de novo kidney transplant recipients, another once-daily formulation already available on the market (Advagraf Ò in Europe; Astagraf XL Ò in the US) failed to demonstrate a reduction in peak concentration in comparison with the twice-daily formulation [30].…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…Increasing pill burden is associated with decreased adherence [20,21], and lack of adherence is associated with acute rejection [22,23] and graft loss [21,[24][25][26]. While there are currently available prolonged-release tacrolimus hard capsule formulations designed for once-daily dosing, data from these formulations do not suggest that they offer improved bioavailability over tacrolimus twice-daily capsules [27][28][29]. In a clinical trial in de novo kidney transplant recipients, another once-daily formulation already available on the market (Advagraf Ò in Europe; Astagraf XL Ò in the US) failed to demonstrate a reduction in peak concentration in comparison with the twice-daily formulation [30].…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…More recently, Krämer and associates published another phase 3 double-blind randomized study in which 667 new kidney recipients received either OD or twice-daily tacrolimus combined with steroids and low-dose mycophenolate. 8 In the per-protocol analysis, the incidence of biopsy-proven acute rejection was slightly higher with tacrolimus OD over 24 weeks (20.4% vs 15.8%; not significant). Graft function, graft loss, patient survival, and adverse reaction profiles were similar among the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are similar to previous published studies. [4][5][6][7][8][9][10][11] We usually do not use ER tacrolimus as induction in de novo kidney transplants as the dosage of tacrolimus is easier to adjust with the twice-daily formulation. However, OD tacrolimus can be useful in patients in whom we want to decrease the initial exposure to calcineurin inhibitors (eg, severe acute tubular necrosis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous pharmacokinetics studies comparing twice-daily and once-daily tacrolimus in de novo transplant recipients have reported that, after once-daily tacrolimus administration, C min values are reduced in the immediate posttransplant period and higher doses of the drug are required to maintain target concentrations. 9,24,25 A previous multicenter comparison of the safety and efficacy of tacrolimus administered once-versus twice-daily to de novo LDLT recipients also demonstrated lower C min values and a higher dose requirement for once daily tacrolimus than for twice-daily tacrolimus when normalized to mr doses of tacrolimus (unpublished data). Here, a higher dose of once-daily tacrolimus was required to maintain target concentrations during the posttransplant period, especially immediately after the conversion from intravenous to oral administration of the drug.…”
Section: Figure 1 Liver Transplantation At Başkent Universitymentioning
confidence: 99%